2021
DOI: 10.1016/j.ijid.2021.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Risk of COVID-19 morbidity and mortality among healthcare workers working in a Large Tertiary Care Hospital

Abstract: OBJECTIVES To estimate COVID-19 infection and outcomes among healthcare workers (HCWs) compared with non-HCWs. METHODS A prospective surveillance study was conducted among HCWs and non-HCWs eligible for treatment at a large tertiary care facility in Riyadh between March 1st to November 30th, 2020. RESULTS A total 13,219 cases with confirmed COVID-19 have been detected during the study; 1596 (12.1%) HCW patients (HCWPs) and 11623 (87.9%) non-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 25 publications
3
40
0
Order By: Relevance
“…Similar to our findings, Al Maskari et al 13 , Mani et al 14 , and Wong et al 15 reported no mortality in their cohorts of 204, 185 and 88 infected HCWs with average ages of 36, 40 and 35 years, respectively. An additional study from Saudi Arabia showed a very low mortality rate of 0.1% among HCWs 12 . On the other hand, more severe outcomes were described in large cohorts of infected HCWs; the CDC COVID-19 working group 16 in their study of 9282 infected HCWs, reported higher hospitalization (9.7%), ICU admissions (4.9%) and mortality rates (0.6%) among all age groups included in the study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar to our findings, Al Maskari et al 13 , Mani et al 14 , and Wong et al 15 reported no mortality in their cohorts of 204, 185 and 88 infected HCWs with average ages of 36, 40 and 35 years, respectively. An additional study from Saudi Arabia showed a very low mortality rate of 0.1% among HCWs 12 . On the other hand, more severe outcomes were described in large cohorts of infected HCWs; the CDC COVID-19 working group 16 in their study of 9282 infected HCWs, reported higher hospitalization (9.7%), ICU admissions (4.9%) and mortality rates (0.6%) among all age groups included in the study.…”
Section: Discussionmentioning
confidence: 97%
“…The latter deserves careful planning and mitigation strategies to prevent the loss of the essential HCW forces during pandemics. Several studies from Saudi Arabia reported the increased frequency of COVID-19 among non-Saudi HCWs with coworkers being a common source of spread of infection especially in the setting of hospital-provided accommodations 10 , 11 , 12 . This finding is probably unique to countries with large numbers of expatriate populations working in healthcare settings and surely creates challenges for infection prevention in these settings.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in physical and verbal violence towards them has also been reported 8 . It has been estimated that healthcare workers have a ten-fold increased risk of being infected by SARS-CoV-2 9 , and this has been sadly confirmed by the large number (at least 115,000 people) of fatalities within the workforce worldwide 10 .…”
Section: Impact Of Covid-19 On Clinical Practitionersmentioning
confidence: 99%
“…In addition, the healthcare workforce in KSA relies mainly on the nursing-related occupation that have more frequent contact and longer exposure time with patients ( Barry et al, 2021 ). In this country, hospital and community settings played both the role of an infection source for HCW ( Barry et al, 2020 ; Alshamrani et al, 2021 ). Healthcare-associated infections include exposure to a positive COVID-19 patient as well as exposure to other infected HCW ( Al Bujayr et al, 2021 ).…”
Section: Healthcare Workersmentioning
confidence: 99%
“…Interestingly, Alshamrani et al conducted a study where they compared the clinical outcomes of infected HCW and non-HCW. They found that the higher risk of ICU admission and hospitalization increases three and two times, respectively in non-HCW compared to HCW ( Alshamrani et al, 2021 ). This could be attributed to the lower comorbidities, younger age, and better awareness of the healthcare personnel ( Alshamrani et al, 2021 ; Gholami et al, 2021 ).…”
Section: Healthcare Workersmentioning
confidence: 99%